Comparison of Intake of Moringa Leaf and Green Beans as an Alternative to Increase Hemoglobin Levels of Pregnant Women With Anemia - Choirunnisa, Aulia; Hidayat, Syarif Thaufik; Supriyana, Supriyana (Devotion : Journal of Research and Community Service, 2023)
Anemia is a "potential danger of mother and child". According to Riskedas (2018) anemia prevalence of pregnant women increased within 5 years from 37.1% to 48.9%. The biggest cause of anemia in pregnancy is iron deficiency anemia. One of the causes is lack of pregnant women get iron tablet (SF) less than 90 tablets and have not consume iron tablets correctly and continuously. Improving iron status can be done with non-pharmacological therapy, including the consumption of moringa and green beans. To compare the effectiveness of Moringa leaves and green beans on hemoglobin levels in pregnant women. Search for articles through the databases of Google Schoolar, Science Direct, PubMed, Elsevier (SCOPUS), Medline using Boolean operators (AND and OR). The research inclusion criteria were : Studies with randomized controlled trial (RCT) or quasi experiment design from 2015 to 2020, research participants were pregnant women, the intervention given was Moringa leaves or green beans. The results of the measurement of hemoglobin levels. Eighteen studies met the eligibility criteria and were analyzed. Moringa leaves were more effective in increasing the hemoglobin level of pregnant women with Standardized Mean Different (SMD) by 0.10 compared to green beans (SMD 0.10; CI 93% = -0.38 to 0.58; p<0.00001). Moringa leaves are more effective in increasing hemoglobin levels of pregnant women than green beans.